Molecular Evaluation of the Mating Dynamics of Snow Crab (Chionoecetes opilio) in the Eastern Bering Sea - Laura M. Slater; William Gaeuman; Wei Cheng; Gordon H. Kruse; Christopher Habicht; Douglas Pengilly (Ecology and Evolution, 2024)
ABSTRACT Snow crab (Chionoecetes opilio) in the eastern Bering Sea (EBS) supports a valuable crab fishery that harvests large males. To better understand the potential impact of the presence of snow‐Tanner hybrids (C. opilio × C. bairdi) on snow crab mating dynamics, the maternal lineage of hybrids was evaluated using single nucleotide polymorphisms (SNPs). Contrary to results from a previous study that indicated hybrids result only from crosses between Tanner crab (C. bairdi) males and snow crab females, results from this study showed hybrids result from bidirectional parental crosses. SNP and microsatellite markers were used to evaluate the species and number of males detected as mates in female sperm reserves acquired during mating and as sires among embryos in brooded clutches. The incidence of interspecies mating between female snow crab and Tanner crab or hybrid males was low (2%), suggesting interspecies mating is not currently a pressing fishery management concern. Most females had stored sperm from either a single mate (59%) or two mates (32%), which reflects fewer mates than observed for other snow crab populations. Few females were observed with either no stored sperm (5%) or sperm from three to four mates (4%). Single (82%) or dual (18%) paternity was found among embryos in brooded clutches. Sperm from some mates appeared to be fully utilized for fertilization of the brooded clutch for 35% of females. In contrast to findings for other snow crab populations, no significant differences were detected in the numbers of mates or sires between primiparous and multiparous females. The low extent of polyandry observed may suggest that female snow crab in the EBS have limited mating opportunities, potentially leading to insufficient sperm reserves to fertilize subsequent clutches without remating.